Synthesis and Characterization of the Chain Borosulfates (NH4)3[B(SO4)3] and Sr[B2(SO4)4]. Issue 18 (5th May 2020) - Netzsch, Philip; Höppe, Henning A.
Abstract : Two new borosulfates were obtained either by an open vessel synthesis from sulfuric acid and B(OH)3, yielding (NH4 )3 [B(SO4 )3 ] or from solvothermal synthesis in oleum enriched sulfuric acid and B(OH)3, yielding Sr[B2 (SO4 )4 ]. (NH4 )3 [B(SO4 )3 ] crystallizes homeotypic to K3 [B(SO4 )3 ] in space group Ibca ( Z = 8, a = 728.58(3) pm, b = 1470.84(7) pm, c = 2270.52(11) pm), comprising open branched vierer single chains 1 ∞ [B(SO4 )2 (SO4 )2/2 ] 3– . Sr[B2 (SO4 )4 ] crystallizes as an ordered variant of Pb[B2 (SO4 )4 ] in space group Pnna ( Z = 4, a = 1257.4(4) pm, b = 1242.1(4) pm, c = 731.9(2) pm), consisting of loop branched vierer single chains 1 ∞ [B(SO4 )4/2 ] 2– . Vibrational spectroscopy confirms both refined structure models. Thermal analysis of the dried powders, showed a decomposition towards the binary and ternary components, whereas a thermal treatment in the presence of the mother liquor promotes a decomposition of Sr[B2 (SO4 )4 ] towards Sr[B2 O(SO4 )3 ]. Abstract :